ITL
© 1996-2015







17 Semantics of Expressions

Let ⟦...⟧e be the “meaning” (semantic) function from Expressions  × Σ to V al (integer values) and let σ0  be a state then

|------------------------------------------|
|⟦z⟧eσ0             =  z                    |
|⟦a⟧eσ              =  σ0(a )               |
|⟦A ⟧eσ0             =  σ0(A )               |
|⟦g(e10,...,en)⟧e   =  g(⟦e1⟧e ,...,⟦en ⟧e )  |
---------------σ0-----------σ0--------σ0----

Example 10

⟦Account  ⟧eσ0            =   σ0(Account )
        e
⟦deposit ⟧σ0             =   σ0(deposit)
⟦Account  + deposit⟧eσ0  =   ⟦Account  ⟧eσ0+ ⟦deposit⟧eσ0
                       =   σ0(Account )+σ0 (deposit)

_____________________________________________________________________